Prostitution and Human Trafficking Focus on Clients - Nicola, Andrea Di.; Cauduro, Andrea.; Lombardi, Marco.; Ruspini, Paolo. (Springer New York, 2009)
While the trafficking of women for prostitution has been the subject of numerous studies, Prostitution and Human Trafficking is the first book to focus on demand as a key factor in the equation. In order to do this, the editors adopted a double approach: on the one hand, a "virtual ethnography" was developed that focused on the analysis of specialized forums on the web and that used an anonymous internet questionnaire as interview method. On the other, fieldwork allowed national research teams to collect interviews and data from likely clients of trafficked prostitutes, prostitutes themselves, from police officers involved and from national experts. Who is the client of trafficked prostitution? What fuels the demand for trafficked prostitution as opposed to other forms? Which are the most effective policies for what type of prostitution? The research in this book aims to answer these questions with an innovative approach. The editors have explored the hidden world of human trafficking for prostitution and profiled its clients. In doing so, they have refuted some common stereotypes about clients while inspiring the elaboration of balanced guidelines for managing prostitution, protecting the victims and thus tackling its undesired trafficking component. Prostitution and Human Trafficking is highly recommended for researchers in the fields of criminology, sociology and law as well as for the law enforcement and legal communities. The book is also recommended for organizations and policymakers involved in fighting organized crime in general and human trafficking in particular.